1950
DOI: 10.1111/j.1365-2672.1950.tb01977.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Overnight Refrigeration on the Results of the Bacteriological Examination of Farm Water Supplies

Abstract: About 20% of water samples examined 20 hr. after sampling, this period including 18 hr. storage at 3-5', had coli-aerogenes and Bact. coli contents significantly lowerlthan those determined after 2 hr. at air temperature. Samples with over 50 such organisms/100 ml. at the earlier testing time seldom showed an increased content after refrigeration overnight. The results of statistical analysis of the data confirmed the findings of other workers that coli-aerogenes bacteria are less abundant in samples of water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1951
1951
1977
1977

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Jones, Franklin & Thomas (1950) found that even when samples were stored a t 3-5" quite appreciable bacterial changes took place. Jones, Franklin & Thomas (1950) found that even when samples were stored a t 3-5" quite appreciable bacterial changes took place.…”
Section: Bacteriological Tests and Their Significancementioning
confidence: 96%
See 1 more Smart Citation
“…Jones, Franklin & Thomas (1950) found that even when samples were stored a t 3-5" quite appreciable bacterial changes took place. Jones, Franklin & Thomas (1950) found that even when samples were stored a t 3-5" quite appreciable bacterial changes took place.…”
Section: Bacteriological Tests and Their Significancementioning
confidence: 96%
“…Samples for bacteriological examination should reach the laboratory as quickly as possible and preferably in less than 6 hr. Jones, Franklin & Thomas (1950) found that even when samples were stored a t 3-5" quite appreciable bacterial changes took place. More detailed investigation by the Public Health Laboratory Service (1953) supported this finding and showed that storage a t room temperature brought about even greater variation.…”
Section: Bacteriological Tests and Their Significancementioning
confidence: 96%
“…A statistical treatment similar to that of Jones, Franklin & Thomas (1950) has been applied to the results. Tables 3 and 4 show a summary of the changes observed in the coli-aerogenes (37") content.…”
Section: Presumptive Coli-aerogenes Contentmentioning
confidence: 99%